Rock brittleness index determination and implementation method suitable for TBM rock breaking energy consumption evaluation

Through the calculation method of rock brittleness index based on the energy conversion mechanism, the complex and cumbersome problems of existing methods are solved, and the direct application at the TBM construction site and the effective evaluation of TBM rock breaking energy consumption is realized.

CN119740355AInactive Publication Date: 2025-04-01YELLOW RIVER ENG CONSULTING CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411689272.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-04-01
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing rock brittleness index calculation methods are complex and cumbersome, and cannot be directly applied to TBM construction sites, especially the research on the characteristics of TBM rock breaking is relatively lacking.

Method used

A method for calculating rock brittleness index based on energy conversion mechanism is proposed. The rock brittleness index BIN is calculated through formula (1), and parameters such as the volume of the rock sample, energy conversion index, uniaxial compressive strength and surface area difference after crushing are used.

Benefits of technology

This method simplifies the calculation process of rock brittleness index, enables it to be directly applied at the construction site, provides an effective evaluation of TBM rock breaking energy consumption, and has an important guiding role in TBM excavation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119740355A_ABST
    Figure CN119740355A_ABST
Patent Text Reader

Abstract

The invention discloses a rock brittleness index determination and implementation method suitable for TBM rock breaking energy consumption evaluation. The method comprises the following steps: preparing a standard rock sample; carrying out a rock uniaxial compression test to measure a rock uniaxial compression strength value; the method comprises the following steps: collecting rock ballasts generated in a rock uniaxial compression test, and carrying out a three-dimensional laser scanning test to measure the surface area of the crushed rock ballasts; establishing an energy conversion index according to the newly increased surface area of the rock sample crushed into rock slag and mechanical energy applied by the test; and calculating the rock brittleness index by combining the uniaxial compressive strength of the rock and the volume of the rock sample. According to the method, a conversion mechanism between mechanical energy and surface energy is considered, the brittleness index evaluation index based on the energy conversion mechanism and considering the rock strength is provided, and the technical problem that the TBM tunneling performance cannot be accurately evaluated through the rock brittleness index in TBM construction is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of rock mechanics, and in particular to a method for determining and implementing a rock brittleness index suitable for evaluating the energy consumption of rock breaking by a TBM. Background Art

[0002] With the rapid development of railway engineering, water diversion engineering and shaft engineering, mechanical excavation methods such as rock tunnel boring machine (TBM) have been widely used. Compared with the traditional drilling and blasting method, the TBM method has the advantages of safety and efficiency, but the geological characteristics of the surrounding rock are one of the key factors affecting the efficiency of TBM excavation. Among them, brittleness is an important indicator for evaluating the machinability and excavability of rock. Accurate evaluation of rock brittleness characteristics can help determine the suitability of construction, predict construction progress and calculate construction costs.

[0003] The brittleness of rocks is usually evaluated by the brittleness index. However, the calculation methods of the brittleness index that have been proposed so far have various deficiencies. First of all, the exploration of rock brittleness index is still mostly concentrated in the indoor test stage and theoretical research. The rock brittleness evaluation methods proposed by some scholars require the construction of complex constitutive models and the fitting of stress-strain curves. The calculation of some parameters involved is relatively complex and cumbersome. It cannot be applied at the construction site at all. There are few reports on the study of rock brittleness index for TBM rock breaking characteristics. Summary of the invention

[0004] The present invention aims to provide a method for determining a rock brittleness index suitable for evaluating the energy consumption of rock breaking by a TBM. Another object of the present invention is to provide a method for implementing a rock brittleness index suitable for evaluating the energy consumption of rock breaking by a TBM, so as to solve the problem that the calculation of the traditional rock brittleness index is complicated and cumbersome and cannot be directly applied to the construction site.

[0005] To achieve the above object, the present invention adopts the following technical solutions: The method for determining the rock brittleness index suitable for evaluating the energy consumption of TBM rock breaking according to the present invention is specifically to calculate the rock brittleness index based on formula (1): BI N ,unit mm -4 ; Formula (1) V is the volume of the rock sample, in mm 3 ; η is the energy conversion index, unit , UCS is the uniaxial compressive strength, Mpa ; , △S is the surface area difference of the rock sample before and after crushing, in mm2 ; W is the total mechanical energy applied to the rock sample from the beginning to the end of the uniaxial compression test, in units of J .

[0006] The implementation method of the rock brittleness index suitable for evaluating the energy consumption of TBM rock breaking according to the present invention specifically comprises the following steps: S1, prepare standard rock samples and rock samples with different water contents; S2, carry out uniaxial compression test on rock samples and measure the uniaxial compressive strength of rock samples in dry and saturated states; S3, performing a three-dimensional scanning test on rock ballast to obtain the surface area of ​​the rock ballast after the rock sample is crushed; S4, calculation of energy conversion index η and rock brittleness index BI N .

[0007] Furthermore, the standard rock sample is a rock core with good drilling depth and integrity at the construction site, and an automatic rock cutting machine is used to cut the rock core into a standard cylindrical rock sample with a diameter of 50 mm and a height of 100 mm.

[0008] Furthermore, the specific steps of preparing rock samples with different water contents include: S1.1, after drying rock samples with different moisture contents at 105 °C for 24 hours, dry rock samples are obtained and the dry rock samples are weighed; S1.2, use the free immersion method to obtain rock samples in dry and saturated states; put the rock sample in a water tank, first fill it with water to 1 / 4 of the height of the rock sample, then fill it with water every 2 hours to 1 / 2 and 3 / 4 of the height of the rock sample respectively, and after 6 hours, the rock sample is completely immersed; after the rock sample is completely immersed in water, it absorbs water freely for 48 hours until it is saturated, then it is taken out, the surface moisture is wiped off and weighed.

[0009] Furthermore, a multifunctional rock direct shear testing machine was used to carry out uniaxial compression tests on rock samples.

[0010] Furthermore, a fully automatic two-axis 3D scanner was used to obtain accurate parameter information of the 3D model of rock slag after the rock sample was destroyed, and Geomagic Studio software was used to process, analyze and count the 3D model of rock slag to obtain the surface area.

[0011] The advantage of the present invention is that it utilizes the newly added surface area after the rock is crushed into rock slag, considers the conversion mechanism between mechanical energy and surface energy, and proposes a brittleness index evaluation method based on the energy conversion mechanism and considering the rock strength. The energy conversion index is established according to the difference between the surface area of ​​the rock sample and the total surface area of ​​the crushed rock slag and the mechanical energy applied in the test. Combined with the uniaxial compressive strength index and the rock sample volume, a new rock brittleness evaluation index calculation formula is established, which has an important guiding role in the evaluation of TBM excavation efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 The present invention is a flow chart of the implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation.

[0013] Figure 2 The figure is a schematic diagram of the standard rock sample preparation process in Example 2 of the present invention.

[0014] Figure 3 This is a schematic diagram of the uniaxial compression test of rock in Example 2 of the present invention.

[0015] Figure 4 This is the three-dimensional scanning test process of rock ballast in Example 2 of the present invention.

[0016] Figure 5 This is a three-dimensional model of the granite slag in Example 2 of the present invention.

[0017] Figure 6 This is a three-dimensional model of the sandstone ballast in Example 2 of the present invention.

[0018] Figure 7 is the rock brittleness index in Example 3 of the present invention Relationship curve with TBM excavation specific energy.

[0019] Figure 8 is the rock brittleness index in Example 3 of the present invention Relationship curve with TBM excavation specific energy.

[0020] Fig. 9 is the rock brittleness index in Example 3 of the present invention Relationship curve with TBM excavation specific energy.

[0021] Fig.10 is the rock brittleness index in Example 3 of the present invention Relationship curve with TBM excavation specific energy. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] Example 1 The method for determining the rock brittleness index suitable for evaluating the energy consumption of TBM rock breaking according to the present invention is specifically to calculate the rock brittleness index based on formula (1): BI N ,unit mm -4 ; Formula (1) V is the volume of the rock sample, in mm 3 ; η is the energy conversion index, unit , UCS is the uniaxial compressive strength, Mpa ; , △S is the surface area difference before and after the rock sample is crushed; W is the total mechanical energy applied to the rock sample from the beginning to the end of the uniaxial compression test, in units of J .

[0024] Its theoretical basis comes from PC Rittinger's new surface theory. The theory points out that the only difference between rock crushing and rock crushing is the addition of new surfaces, and the energy required to obtain new surfaces is proportional to the crushing work. Based on this theory, the proportion of the newly added surface of rock debris to the total mechanical energy after rock crushing can reflect the brittleness of the rock.

[0025] Based on this theory, the inventor introduced the energy conversion index η , ;in, W It is the total mechanical energy applied to the rock sample from the beginning to the end of the uniaxial compression test, in units of J ; It is the vertical force acting on the specimen during the uniaxial compression test of rock, in units of N S1 is the total surface area of ​​rock debris after the rock sample is crushed, in mm 2 ; S0 is the surface area of ​​the rock sample before crushing, in mm 2 ; △S is the surface area difference of the rock sample before and after crushing, in mm 2 . η The unit is mm / N .

[0026] Based on the energy conversion index η and the uniaxial compressive strength of rock, the calculation formula of the rock brittleness index BIN is constructed, as shown in formula (1).

[0027] The method for calculating the rock brittleness index proposed in the present invention based on the energy conversion mechanism can quantitatively characterize the energy conversion efficiency, provide a scientific reference for the energy conversion evaluation during TBM excavation and rock breaking, and is an effective method for TBM performance evaluation.

[0028] Based on the method for calculating the rock brittleness index of the present invention, the present invention proposes a method for implementing the rock brittleness index suitable for TBM rock breaking energy consumption evaluation directly applied in on-site construction, such as Figure 1 As shown, the specific steps include: S1, prepare standard rock samples and rock samples with different water contents.

[0029] The standard rock samples were prepared according to the standard rock sample preparation method of "Engineering Rock Test Method Standard" (GB / T50266-2013). At the construction site, cores with the same drilling depth and good integrity were selected, and an automatic rock cutting machine was used to cut the core samples into standard cylindrical rock samples with a diameter of 50 mm and a height of 100 mm.

[0030] The preparation of rock samples with different water contents specifically includes: S1.1, after drying rock samples with different moisture contents at 105 ℃ for 24 hours, dry rock samples are obtained and weighed.

[0031] S1.2, use the free immersion method to obtain rock samples in dry and saturated states; put the rock sample in a water tank, first fill it with water to 1 / 4 of the height of the rock sample, then fill it with water every 2 hours to 1 / 2 and 3 / 4 of the height of the rock sample respectively, and after 6 hours, the rock sample is completely immersed; after the rock sample is completely immersed in water, it absorbs water freely for 48 hours until it is saturated, then it is taken out, the surface moisture is wiped off and weighed.

[0032] S2, carry out uniaxial compression test on rock samples, and measure the uniaxial compressive strength of rock samples in dry and saturated states at the same time.

[0033] Generally, a multifunctional rock direct shear testing machine can be used. The rock sample can be placed in the testing machine and the machine can be started to carry out a uniaxial compressive strength test. After the test is completed, the test bench should be carefully cleaned to ensure that all the rock debris that falls around the platform when the rock sample fails brittlely can be collected.

[0034] S3, conduct a three-dimensional scanning test of rock slag to obtain the surface area of ​​the rock slag after the rock sample is crushed.

[0035] The 3D scanning test of rock ballast used a modified highly integrated fully automatic dual-axis 3D scanner designed based on the application scenario of 3D reconstruction of fine small workpieces to carry out 3D scanning tests on rock ballast after the uniaxial compression test. The accurate 3D model parameter information of rock ballast after the rock sample was destroyed was obtained through 3D scanning, and the scanning results were automatically generated in STL standard format. The 3D models of granite and sandstone rock ballast were processed, analyzed and counted using Geomagic Studio software to obtain their surface area information.

[0036] S4, calculation of energy conversion index η and rock brittleness index BI N .

[0037] Example 2 At the construction site, standard rock samples were prepared according to the Standard for Engineering Rock Mass Test Methods (GB / T50266-2013). The core samples were cut into standard cylindrical rock samples with a diameter of 50 mm and a height of 100 mm using an automatic rock cutting machine. Figure 2 shown.

[0038] The granite and sandstone standard rock samples were divided into different water content test groups (granite G1-G8, sandstone S1-S8) and natural state test groups (granite G9-G16, sandstone S9-S16). Next, standard rock samples with different water content were prepared respectively.

[0039] First, the rock samples with different moisture contents were dried at 105 °C for 24 hours to obtain dry rock samples, and then the dry rock samples were weighed. The free immersion method was used to obtain the rock samples in dry and saturated states. The rock samples were placed in a water tank, and water was first injected to 1 / 4 of the rock sample height. Then, water was injected to 1 / 2 and 3 / 4 of the rock sample height every 2 hours. After 6 hours, all the rock samples were immersed. After all the rock samples were immersed in water, they were freely absorbed for 1, 2, 4, 8, 12, 24 and 48 hours until they were saturated and taken out. The surface moisture was wiped off and weighed. The moisture content of different rock samples is shown in Table 1.

[0040] Table 1 The instrument used for granite is a fully automatic constant stress pressure testing machine, and the instrument used for sandstone is a multifunctional rock direct shear testing machine. The test is carried out in accordance with the relevant requirements of the ISRM standard. Figure 3 The test results are shown in Table 2.

[0041] Table 2 Uniaxial compressive strength of rocks The rock slag obtained from the uniaxial compressive strength test was subjected to a 3D scanning test. The surface area of ​​the rock slag after rock crushing was obtained by 3D laser scanning. The 3D scanning test of rock slag used a highly integrated fully automatic dual-axis 3D scanner (Scan-T100) designed based on the application scenario of 3D reconstruction of fine small workpieces (<150mm). Figure 4 The scanning results are automatically generated in STL standard format. The surface area information of granite and sandstone rock slag can be obtained by processing, analyzing and counting the three-dimensional models of granite and sandstone rock slag using Geomagic Studio software. Figure 5 , Figure 6 The parameter information of the rock ballast 3D model is shown in Table 3.

[0042] Table 3 Parameter information of rock ballast 3D model The calculation results of energy conversion index η and rock brittleness index BIN are shown in Table 4.

[0043] Table 4 Calculation results of energy conversion index and brittleness index during uniaxial compression test of rock Example 3 The implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation described in the present invention is combined with TBM engineering to verify the applicability of the index.

[0044] At the construction site of the biotite granite excavation section during the TBM construction of a water diversion project in a certain place, a total of eight biotite granite excavation sections were selected, of which four sections were in a dry state and the other four sections were in a saturated state. The cores with the same drilling depth and good integrity were selected, and standard rock samples were prepared according to the "Standard for Engineering Rock Test Methods" (GB / T50266-2013). The core samples were cut into standard cylindrical rock samples with a diameter of 50 mm and a height of 100 mm using an automatic rock cutting machine. The standard biotite granite cores of each excavation section obtained for the uniaxial compression test were sealed in time to maintain their original dry and wet states.

[0045] The uniaxial compressive test of rock was carried out, and the uniaxial compressive strength of rock in dry and saturated state was measured at the same time. The specific results are shown in Table 5.

[0046] Table 5 Uniaxial compressive strength values ​​of biotite granite Step 3: Conduct a three-dimensional scanning test of rock slag, obtain the surface area of ​​the rock slag after the rock is crushed by three-dimensional laser scanning, repeat step 4 of embodiment 1, and the parameter information of the three-dimensional model of biotite granite rock slag is shown in Table 6.

[0047] Table 6 Parameter information of the three-dimensional model of biotite granite ballast Step 4: Calculate energy conversion index The energy conversion index is calculated by the formula based on the difference between the total surface area of ​​the rock ballast and the surface area of ​​the rock sample and the total mechanical energy applied from the beginning to the end of the uniaxial compression test. .

[0048] Step 5: Use the energy conversion evaluation index and the uniaxial compressive strength of rock to calculate the rock brittleness evaluation index BI N .

[0049] At the same time, other proposed rock brittleness indexes are calculated, and the relationship between each brittleness index and rock excavability is compared. The calculation formulas for the other three different brittleness indexes (B2, B3, and B4) are as follows: Where: B2, B3, B4 are the brittleness indexes obtained by different calculation methods, σ c is the uniaxial compressive strength, unit: MPa. t It is the uniaxial tensile strength, unit is MPa.

[0050] The calculation results of brittleness index of various types of rocks are shown in Table 7.

[0051] Table 7 Calculation results of rock brittleness index Since the TBM excavation rate increases with the increase of rock brittleness, specific energy (SE) is the work required for the TBM cutter to cut a unit volume of rock. It is an important indicator to measure the rock breaking efficiency of the TBM. By collecting the measured data on site, the average specific energy of the corresponding excavation sections can be calculated for the eight selected TBM excavation sections. The specific energy of different excavation sections is shown in Table 8.

[0052] Table 8 Specific energy of different TBM excavation sections The specific energy of dry and saturated biotite granite surrounding rock under excavation conditions and the brittleness index of the surrounding rock in the corresponding excavation section ( , , and ) to conduct correlation analysis, such as Figure 7 , Figure 8 , Fig. 9 , Fig.10 shown.

[0053] Depend on Figure 7 It can be seen that whether the biotite granite is in a dry state or a saturated state, the TBM excavation specific energy increases with the rock brittleness index. In general, the specific energy and rock brittleness index , and The fitting relationship is relatively poor. The reason is that the rock brittleness index , and Only considering the uniaxial compressive strength and uniaxial tensile strength of rock, it cannot truly reflect the complex rock-machine interaction mechanism in the TBM rock breaking process. It is based on the energy conversion mechanism in the process of TBM rock breaking and takes into account the rock strength characteristics, which can more comprehensively and deeply reflect the rock-machine interaction mechanism. , and , the rock brittleness index proposed It is more suitable for TBM rock breaking energy consumption evaluation and analysis.

Claims

1. A method for determining rock brittleness index suitable for evaluating TBM rock breaking energy consumption, characterized by: Calculate the rock brittleness index based on formula (1) BI N ,unit mm -4 ; Formula (1) V is the volume of the rock sample, in mm 3 ; η is the energy conversion index, unit , UCS is the uniaxial compressive strength, Mpa ; , △S is the surface area difference of the rock sample before and after crushing, in mm 2 ; W is the total mechanical energy applied to the rock sample from the beginning to the end of the uniaxial compression test, in units of J .

2. A method for implementing the rock brittleness index suitable for evaluating the energy consumption of TBM rock breaking, characterized by: The following steps are included: S1, prepare standard rock samples and rock samples with different water contents; S2, carry out uniaxial compression test on rock samples and measure the uniaxial compressive strength of rock samples in dry and saturated states; S3, performing a three-dimensional scanning test on rock ballast to obtain the surface area of ​​the rock ballast after the rock sample is crushed; S4, calculation of energy conversion index η and rock brittleness index BI N .

3. The implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation according to claim 2 is characterized by: The standard rock sample is a rock core with good drilling depth and integrity at the construction site, and an automatic rock cutting machine is used to cut the rock core into a standard cylindrical rock sample with a diameter of 50 mm and a height of 100 mm.

4. The implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation according to claim 2 is characterized by: The specific steps of preparing rock samples with different water contents include: S1.1, after drying rock samples with different moisture contents at 105 °C for 24 hours, dry rock samples are obtained and the dry rock samples are weighed; S1.2, use the free immersion method to obtain rock samples in dry and saturated states; put the rock sample in a water tank, first fill it with water to 1 / 4 of the height of the rock sample, then fill it with water every 2 hours to 1 / 2 and 3 / 4 of the height of the rock sample respectively, and after 6 hours, the rock sample is completely immersed; after the rock sample is completely immersed in water, it absorbs water freely for 48 hours until it is saturated, then it is taken out, the surface moisture is wiped off and weighed.

5. The implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation according to claim 2 is characterized by: A multifunctional rock direct shear testing machine is used to carry out uniaxial compression tests on rock samples.

6. The implementation method of the rock brittleness index suitable for TBM rock breaking energy consumption evaluation according to claim 2 is characterized by: A fully automatic two-axis 3D scanner was used to obtain accurate parameter information of the 3D model of rock slag after rock sample destruction, and Geomagic Studio software was used to process, analyze and count the 3D model of rock slag to obtain the surface area.

Citation Information

Cited By

  • Layered rock mass tunnel face sampling method

    CN120427306A